Contesting natural resource development in Canada: the legacies and limits of the staples approach. Issue 2 (September 2018) - Bowles, Paul; MacPhail, Fiona
Abstract : Harold Innis (1930) famously described Canada as a country comprised of 'hewers of wood and drawers of water'. The staples approach that he advanced and which his followers subsequently further developed has become a reference point for continuing debate over the economic importance and consequences of natural resource development in Canada, a debate reignited by the long commodities boom of 2000–14. In this article we examine another, overlooked legacy of the staples approach, namely, the ways in which its emphasis on linkages has provided a frame of reference for opponents of natural resource projects. This is illustrated by examining some of the contemporary contestations of resource projects in northern British Columbia. These examples also show, however, that the staples approach provides only a partial frame of reference for contemporary contestations; more recent concerns such as Indigenous rights, procedural fairness, and environmental issues also play a significant role in oppositional politics to resource projects. Nevertheless, our discussion shows that Canada at 150 is still debating the role that natural resource development should play, and that the legacy of the staples approach continues to play a role in the debate.